2014
DOI: 10.1177/1071100714540893
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lag Screw Versus Buttress Plate Fixation of Posterior Malleolar Fractures

Abstract: Level II, prospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 22 publications
3
66
0
Order By: Relevance
“…Choi reported a mean AOFAS score of 90.6 following ORIF of PMF through a modified posterolateral approach [28]. Erdem achieved a mean AOFAS score of 94.1 of PMF following posterior-to-anterior lag screw fixation or buttress plate fixation through posterolateral approach [30]. Compared with our study, the patients with a PMF smaller than 25% of articular surface were included in these studies, which might contribute to the higher AOFAS scores reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Choi reported a mean AOFAS score of 90.6 following ORIF of PMF through a modified posterolateral approach [28]. Erdem achieved a mean AOFAS score of 94.1 of PMF following posterior-to-anterior lag screw fixation or buttress plate fixation through posterolateral approach [30]. Compared with our study, the patients with a PMF smaller than 25% of articular surface were included in these studies, which might contribute to the higher AOFAS scores reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The method of posterior malleolar fixation is controversial. Erdem et al compared the clinical and radiographic outcomes of the use of either lag-screw fixation or buttress-plate fixation through a posterolateral approach 10 . After a mean follow-up of 3 years, all fractures achieved union and no difference in AOFAS scores was observed between the treatment groups.…”
Section: Ankle Fractures and Syndesmotic Injuriesmentioning
confidence: 99%
“…[5,7,13] It is thought that it might reduce development of OA, which would ultimately result in better function. As of yet, however, there is no good scientific evidence of this.…”
Section: Discussionmentioning
confidence: 99%
“…[2,6,10] Based on biomechanical, cadaveric, and small population studies, fragment size is frequently cited as one of the main indications for fixation with thresholds for surgery ranging from 25% to 33% of the anteroposterior (AP) dimension of the articular surface. [2,[10][11][12][13] However, thus far there has not been any strong clinical evidence and no consensus.…”
Section: Introductionmentioning
confidence: 99%